PROBLEMS OF EMPLOYMENT AND SOCIAL PROTECTION (International Conference on Scientific Research in Natural and Social Sciences, 2025)
In our country, in recent years, strengthening social protection of citizens and reducing poverty have been identified as a priority area of state policy in terms of reforming the national economy, and providing the population with new jobs and a guaranteed source of income, qualified medical and educational services, and decent living conditions have reached a qualitatively new level. As a result of the reforms carried out over the past five years, the necessary political, legal, socio-economic, and scientific and educational foundations for building a New Uzbekistan have been created in our country.